The impact of the personal finance management of Stanlib Lesotho on investment behaviour of Maseru teachers - Mohoanyane, Monddy Maretsepile (University of the Free State, 2015)
Financial markets today are infused with a vast array of investment opportunities and products adding benefits in terms of liquidity, flexibility, affordability, diversification and professional management. However, individuals are not always using the investment opportunities. As a means to promote financial education in Lesotho, STANLIB Lesotho partook in SUFIL (Support to Financial Inclusion in Lesotho), an initiative collaborated by the Central Bank of Lesotho and UNDP (United Nations Development Programme) that launched a campaign aimed at increasing individual financial awareness in the country as well as motivate the Basotho people to improve their money management skills. STANLIB has taken diligent measures of ensuring increased financial awareness as well as product awareness among Maseru teachers in the country, and yet very few teachers invest in the company’s products. This makes it difficult to measure and determine whether programmes put in place are effective. It is unclear whether investors’ understanding of financial products and concepts is clear and whether they can make more informed choices and effective decisions to improve their financial wellbeing. The aim of this study was therefore to explore the impact of the personal finance management education of STANLIB Lesotho on the investment behavior of Maseru teachers. The teachers in six high schools around the Maseru district have been chosen for this research comprising the sample of 192 people. Questionnaires on financial planning were personally administered and then analysed. The results show that more teachers responded positively to financial planning than teachers who responded negatively. They understand the importance of financial planning and are diligently maintaining their planning and records of their spending and saving. However, a significant 78.4 % of the respondents indicated dissatisfaction with their current savings and investments, while only 21.6 % were satisfied. Furthermore, the study uncovers a substantial ignorance when it comes to retirement planning and pension fund planning. Only 58.55 % of the respondents have indicated they are members of the government pension fund, while there is a concerning 41.45 % who are not members of a pension fund upon retirement.
Dissertation (MBA (Business Administration))--University of the Free State, 2015
Keywords: Teachers -- Lesotho; Finance, Personal; Finance -- Planning; Retirement -- Planning; Investments